Bacterial Community Selection of Russula griseocarnosa Mycosphere Soil - Yu, Fei; Liang, Jun-Feng; Song, Jie; Wang, Sheng-Kun; Lu, Jun-Kun (Frontiers in Microbiology, 2020)
Russula griseocarnosa is a wild, ectomycorrhizal, edible, and medicinal fungus with high economic value in southern China. R. griseocarnosa fruiting bodies cannot be artificially cultivated. To better understand the effects of abiotic and biotic factors on R. griseocarnosa growth, the physicochemical properties of R. griseocarnosa and its associated bacterial communities were investigated in two soil types (mycosphere and bulk soil) from Fujian, Guangdong, and Guangxi Provinces. The results revealed that the diversity, community structure, and functional characteristics of the dominant mycosphere bacteria in all geographical locations were similar. Soil pH and available nitrogen (AN) are the major factors influencing the mycosphere–soil bacterial communities’ structure. The diversity of soil bacteria is decreased in R. griseocarnosa mycosphere when compared with the bulk soil. Burkholderia-Paraburkholderia, Mycobacterium, Roseiarcus, Sorangium, Acidobacterium, and Singulisphaera may also be mycorrhiza helper bacteria (MHB) of R. griseocarnosa. The functional traits related to the two-component system, bacterial secretion system, tyrosine metabolism, biosynthesis of unsaturated fatty acids, and metabolism of cofactors and vitamins were more abundant in R. griseocarnosa mycosphere soil. The mycosphere soil bacteria of R. griseocarnosa play a key role in R. griseocarnosa growth. Application of management strategies, such as N fertilizer and microbial fertilizer containing MHB, may promote the conservation, propagation promotion, and sustainable utilization of R. griseocarnosa.